The Relationship of Exclusive Breastfeeding History to Morbidity In Infants Aged 1-14 Months - Lani Gumilang; Neneng Martini; Sefita Aryuti Nirmala; Meita Dhamayanti (Universitas Andalas, 2020)
Objectives: This study aims at determining the relationship between the history of exclusive breastfeeding and morbidity in babies aged 1-14 months in the city of Sukabumi.Materials and Methods: This study uses a cross-sectional method with a sample of 71 babies aged 1-14 months in the city of Sukabumi. Data sources used are primary and secondary data, and the Spearman test is used for dataanalysis.Results: The results showed that there was no relationship between the history of exclusive breastfeeding and ISPA (p=1,000), there was no relationship between the history of exclusive breastfeeding and diarrhea (p=1,000), there was no relationship between the history of exclusive breastfeeding and fever (p=0,477), there is no relationship between the history of exclusive breastfeeding and seizures (p=1,000), there is no relationship between the history of exclusive breastfeeding and pneumonia (p=1,000).Conclusion: The study concludes that there is no relationship between the history of exclusive breastfeeding and morbidities namely ISPA, diarrhea, fever, seizures and pneumonia in babies aged 1-14 months in the city of Sukabumi.Keywords: Exclusive breastfeeding, morbidity